O Brasil e a assistência humanitária internacional: prática, discurso e tendências - Tambourgi, Patrícia Vilarinho (2012)
This study aims to assess the affections found in adolescents living in temporary institutional housing, in interface with the institution knowledge, and to raise the reflection about the processes of subjection and autonomy. For better understanding the concepts of passivity and autonomy this study counts on the theoretical support available in literature of important philosophers as Espinosa and Foucault. The qualitative method was selected and the study was structured based on the genealogy of Michel Foucault assessing the power relations and highlighting the knowledge, not yet scientifically recognized, built up based in daily experiences of life. Nine teenagers, temporarily living in two institutional housing (one being governmental and the other a religious-oriented institution), were evaluated. They reveal possibilities of actions concerning resistance and autonomy. We should also point out the importance to approach a topic not previously considered in the research objectives: the regimes of truth and the process of subjectivation of youth is not a direct relation. It is indeed mediated by their families, on whom such regimes of truth is addressed being often evaluated, claimed and standardized and sometimes blamed for the need of housing as well as for the delay on reunification. There is a sequence of actions expressed or implied to be accomplished as a previous condition for reunification. In one of the institutions the evaluation targeted the youngster condition, not the family structure. Importantly to be mentioned that, in certain processes, there was a dissonance in what refers the moral way housing institutions would see these families versus the chance of the technical service and Child and Youth Court of Law, as required by the Statute of the Child and Adolescent, to recognize the possibility that these families could reassume taking care of their children